2015
DOI: 10.1073/pnas.1518648113
|View full text |Cite
|
Sign up to set email alerts
|

A ribosome-inactivating protein in a Drosophila defensive symbiont

Abstract: Vertically transmitted symbionts that protect their hosts against parasites and pathogens are well known from insects, yet the underlying mechanisms of symbiont-mediated defense are largely unclear. A striking example of an ecologically important defensive symbiosis involves the woodland fly Drosophila neotestacea, which is protected by the bacterial endosymbiont Spiroplasma when parasitized by the nematode Howardula aoronymphium. The benefit of this defense strategy has led to the rapid spread of Spiroplasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
117
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 53 publications
6
117
0
Order By: Relevance
“…neotestacea , and that depurinates at the α-sarcin/ricin loop of eukaryotic 28S rRNA [32,40]. Interestingly, the Spiroplasma from D .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…neotestacea , and that depurinates at the α-sarcin/ricin loop of eukaryotic 28S rRNA [32,40]. Interestingly, the Spiroplasma from D .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, infection experiments revealed that nematodes that infect flies harbouring Spiroplasma exhibit the hallmarks of attack by RIP toxins, including massive increases in levels of depurinated ribosomes [40]. Intriguingly, the genome of the Spiroplasma symbiont of D .…”
Section: Introductionmentioning
confidence: 99%
“…The great majority of animals harbour gut microorganisms of variable composition (Brooks, Kohl, Brucker, van Opstal & Bordenstein, ; McFall‐Ngai et al., ), and there is increasing evidence that this microbial variation can influence the phenotype of the host (Hamilton, Peng, Boulanger & Perlman, ; Kohl, Weiss, Cox, Dale & Dearing, ; Sampson et al., ; Surana & Kasper, ). However, most of the studies investigating the relationship between the gut microbiome and host traits have two important limitations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, protection against a virulent nematode (Howardula aoronymphium) by Spiroplasma through the production of a toxin has been observed in Drosophila neotestacea, illustrating the positive effect these interactions can have in the defense system of the hosts (Douglas, 2011;Hamilton et al, 2015). Another example is the bacteria in the digestive tract of insects that appear to be necessary for detoxification of plant material (Bugg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%